Fatigue of natural rubber under different temperatures. (July 2019) - Ruellan, B.; Le Cam, J.-B.; Jeanneau, I.; Canévet, F.; Mortier, F.; Robin, E.
Highlights: Temperature effects on the fatigue life reinforcement due to SIC are investigated. Damage modes and number of cycles at crack initiation are mapped in the Haigh diagram. The signature of SIC reinforcement in the crack growth mechanisms is identified. At 90 °C, fatigue life reinforcement is still observed. At 110°C, the fatigue life reinforcement totally disappears. Abstract: Natural rubbers have extraordinary physical properties, typically the ability to crystallize under tension that is assumed to be responsible for their high fatigue resistance. Strain-induced crystallization (SIC) is a high thermo-sensitive phenomenon. Better understanding how SIC reinforces fatigue life and how temperature affects this property is therefore a key point to improve the durability of rubbers. The present study investigates temperature effects on the fatigue life reinforcement due to SIC for non-relaxing loadings. After a brief state of the art that highlights a lack of experimental results in this field, a fatigue test campaign has been defined and was carried out. Results obtained at 23 °C were first described at the macroscopic scale. Both damage modes and number of cycles at crack initiation were mapped in the Haigh diagram. Fatigue damage mechanisms were then investigated at the microscopic scale, where the signature of SIC reinforcement in the crack growth mechanisms has been identified. Typically, fatigue striations, wrenchings and cones peopled the fracture surfaces obtained under non-relaxing loading conditions. At 90 °C, fatigue life reinforcement was still observed. It is lower than at 23 °C. Only one damage mode was observed at the macroscopic scale. At the microscopic scale, fracture surfaces looked like the ones of non-crystallizable rubbers. At 110 °C, the fatigue life reinforcement totally disappeared.